(untitled) (Journal of Nobel Medical College, 2022)
Uncontrolled hypertension being the most important risk factor for intracerebral hemorrhage (ICH) often leads to solitary hematoma whereas multiple spontaneous simultaneous ICH is not common, and occurrence of bilateral hemorrhage is a rare entity with normal bleeding parameters with very few case reports so far. Here, we report a 67-year-old man with a past medical history of uncontrolled hypertension who was brought to the emergency department due to severe headache, worsening confusion for 1 day. An urgent non-contrast brain Computed Tomography (CT) performed immediately revealed bilateral intracerebral hemorrhage (ICH) of the same age in the right putamen and left thalamus. Our patient had a non-traumatic ICH, with low GCS (5/15) at presentation. He was managed conservatively with antihypertensives and antiedema measures. He was discharged in stable condition GCS 14/15 with left hemiparesis (3/5). At last follow up he was recovering well.Due to the rarity of spontaneous intracranial bleed in patient with normal bleeding parameters, it is particularly interesting to report this rare case presentation.